The Spanish Civil War : revolution and counterrevolution - Bolloten, Burnett; Payne, Stanley G.; Esenwein, George (Chapel Hill : University of North Carolina Press, 2015)
Annotation This monumental book offers a comprehensive history and analysis of Republican political life during the Spanish Civil War. Completed by Burnett Bolloten just before his death in 1987 and first published in English in 1991, "The Spanish Civil War" is the culmination of fifty years of dedicated and painstaking research and is the most exhaustive study on the subject in any language. It has been regarded as the authoritative political history of the war and an indispensable encyclopedic guide to Republican affairs during the Spanish conflict. This new edition includes a new introduction by Spanish Civil War scholar George Esenwein, an updated bibliography featuring books on the Spanish Civil War published since 1987, and seventy-three photos of the war's participants
44. The Overthrow of Largo Caballero45. The Rise of Juan Negrín; Part VI: The Reflux of the Revolution; 46. The Negrín Government and the Reaction of the Libertarian Movement; 47. The PSUC Supersedes the CNT and FAI as the Dominant Force in Catalonia; 48. Communist Repression of the Anarchists and the POUM; 49. Highlights of the POUM Trial; 50. The Destruction of the Agricultural Collectives and the Council of Aragon; Part VII: The Eclipse of Largo Caballero and Indalecio Prieto; 51. Indalecio Prieto Challenges the PCE; 52. The PCE Courts the CNT.
Print version record.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed October 12, 2015).
JSTOR
Keywords: Negrin, Juan; Negrín, Juan; Partido Comunista de España -- History; Negrín, Juan; Partido Comunista de España; Communism -- Spain -- History; Spain -- History -- Civil War, 1936-1939.; Spain -- Politics and government -- 1931-1939.; Espagne -- Histoire -- 1936-1939 (Guerre civile); Espagne -- Politique et gouvernement -- 1931-1939.; HISTORY -- Europe -- Spain & Portugal; HISTORY -- Military -- Other; Communism; Politics and government; Spain; 1931-1939; History